Pengaruh Pemahaman Agama Islam terhadap Penggunaan Hijab Siswi Sesuai Syariat (Kelas 11 SMA Insan Kamil Kota Bogor) - Nurhasanah, Siti Yuni; Indriya, Indriya; Hamdani, Ikhwan (Lembaga Yasin AlSys, 2025)
The phenomenon of hijab use among Muslim female adolescents reflects a shift, where some students tend to wear the hijab in a fashionable manner that does not align with Islamic legal prescriptions, such as using transparent hijabs or not fully covering the hair. This study aims to analyze the influence of Islamic religious understanding on wearing the hijab according to sharia among eleventh-grade students at SMA Insan Kamil Bogor. A quantitative approach was employed using a survey method, with data collected through questionnaires distributed to 74 respondents selected using purposive sampling. The research instrument was tested for validity and reliability, while data analysis was conducted using simple linear regression with the aid of SPSS software. The results show that Islamic religious understanding has a significant influence on sharia-compliant hijab use, with an R Square value of 0.188, indicating that 18.8% of the variability in hijab use can be explained by the level of Islamic understanding. The significance test yielded a p-value of 0.000 (< 0.05), thus the hypothesis is accepted. These findings indicate that the higher the level of Islamic understanding, the greater the tendency for students to wear the hijab in accordance with sharia. In conclusion, although Islamic religious understanding has a significant influence, other factors also affect hijab-wearing behavior. Therefore, there is a need to strengthen Islamic understanding through education and the cultivation of religious values to ensure consistent adherence to sharia-compliant hijab use.